Effects of Synchronous Whole Body Vibration Training on a Soft, Unstable Surface in Athletes with Chronic Ankle Instability - Sierra-Guzmán, Rafael; Jiménez, Jose Fernando; Ramírez, Carlos; Esteban, Paula; Abián-Vicén, Javier (International Journal of Sports Medicine, 2017)
The aim of this study was to evaluate the effects of a 6-week WBV training program, performed on a soft, unstable surface, on peak torque, reaction time and the electrical activity of ankle muscles in recreational athletes with chronic ankle instability (CAI). 50 recreational athletes with self-reported unilateral CAI were randomly assigned to a vibration group (VIB), non-vibration group (N-VIB) or control group. The VIB and N-VIB groups performed unilateral balance training on the unstable ankle on a BOSU® Balance Trainer 3 times weekly for 6 weeks. The VIB group trained on a vibration platform, and the N-VIB group trained on the floor. Muscle reaction times and electrical activity of the peroneus brevis (PB), peroneus longus (PL) and tibialis anterior (TA) muscles were assessed in response to sudden inversion, isokinetic peak torque and isokinetic strength ratios of the ankle evertor muscles. After 6 weeks of training, a significant improvement was shown in reaction times of the PB (Pre=60.99±9.17 ms, Post1=54.90±6.99 ms, p=0.003), PL (Pre=61.20±10.72 ms, Post1=55.21±9.04 ms, p=0.007) and TA (Pre=65.31±11.78 ms, Post1=59.07±9.99 ms, p=0.007) muscles in the VIB group, whereas no significant changes were found in the N-VIB group or the control group. There were no significant changes in electrical activity, peak torque and eccentric-concentric ratio for any of the groups after training. In conclusion, a 6-week WBV training program on a soft, unstable surface improves the reaction times of the PB, PL and TA muscles in recreational athletes with CAI.Trial registration: ClinicalTrials.gov NCT02794194
Keywords: electromyography; ankle instability; isokinetic; proprioceptive training; vibrating platform; strength